2011
DOI: 10.1111/j.1553-2712.2011.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Hospital Admissions at Emergency Department Triage Using Routine Administrative Data

Abstract: Objectives: To be able to predict, at the time of triage, whether a need for hospital admission exists for emergency department (ED) patients may constitute useful information that could contribute to systemwide hospital changes designed to improve ED throughput. The objective of this study was to develop and validate a predictive model to assess whether a patient is likely to require inpatient admission at the time of ED triage, using routine hospital administrative data.Methods: Data collected at the time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
154
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(165 citation statements)
references
References 20 publications
9
154
2
Order By: Relevance
“…Our admission rate was similar to that reported in a Canadian study 27 (38% admission rate of ambulance arrivals), but lower than that seen in a study undertaken in Singapore (59% admission rate for ambulance arrivals). 28 The Canadian study further revealed that people arriving to the ED via ambulance had admission odds 3.15-fold those of people arriving via other means. 27 These figures indicate that further identification of specific predictors of admission used to facilitate targeted service delivery and patient flow may be useful.…”
Section: Prevalence and Predictors Of Hospital Admissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our admission rate was similar to that reported in a Canadian study 27 (38% admission rate of ambulance arrivals), but lower than that seen in a study undertaken in Singapore (59% admission rate for ambulance arrivals). 28 The Canadian study further revealed that people arriving to the ED via ambulance had admission odds 3.15-fold those of people arriving via other means. 27 These figures indicate that further identification of specific predictors of admission used to facilitate targeted service delivery and patient flow may be useful.…”
Section: Prevalence and Predictors Of Hospital Admissionmentioning
confidence: 99%
“…Regarding age, several studies have identified an admission rate of approximately 65% for people aged 65 years. 28,29 Within this demographic, higher odds of admission were related to increasing patient age, higher heart rate, lower blood pressure, lower triage score and several chief complaints, such as pneumonia and stroke. 29 Knowing that older people (particularly those arriving via ambulance) comprise a high proportion of and likelihood for admission, it is possible to use this and other predictive information, such as that offered by LaMantia et al, 29 to order an in-patient bed at the point of triage, thus avoiding delays in admission.…”
Section: Prevalence and Predictors Of Hospital Admissionmentioning
confidence: 99%
“…Also, a system capable of accurately establishing the probabilities of inpatient admission (hospitalization) for every ED patient right after triage can help streamline operations and establish priorities for clinical personnel, bed managers and supporting personnel. Previous research had shown that clinical triage 1 personnel could not predict the need for inpatient admission with sufficient reliability [21][22][23], however, models with a manageable number of easily-obtainable variables and a simple procedure for calculating the probabilities of admission could be used to aid in this task [24][25][26]. In both cases (ED census forecasts and prediction of probabilities of inpatient admission from the ED) predictive models with varying degrees of sophistication can be developed.…”
Section: Glossary Of Terms and Abbreviationsmentioning
confidence: 99%
“…Examples of these are the total number of pharmacy dispensations in primary care [24] for a given patient, or standardized chronic clinical conditions [25], which are not available in all EDs of specialized care hospitals in real time (or at all). Also, several models relied on variables which were highly specific to a country or a region [25,26], which made them impossible to apply in other regional settings.…”
Section: Glossary Of Terms and Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation